Dose caffeinated energy drink is a consideration issue for endurance performance - Wang, Jie-Ping; Wei, Chen-Chan; Peng, Yun-Dong; Wang, Hsuan-Yun; Hung, Chi-Hsiang; Hong, Yin-Hui; Liou, Yuh-Feng; Hou, Chien-Wen (Frontiers in Physiology, 2022)
Energy drinks are commonly taken to improve exercise performance, but there are few studies on the influence of different doses on an athlete’s performance. We conducted a double-blind, randomized, counter-balanced, and crossover research study to examine the effects of varied doses of energy drink consumption on the performance, haematological response, and oxidative stress in triathletes. Enrolled participants underwent three testing sessions separated by weekly intervals, consisting of sprint triathlon training (0.75 km swim, 20 km cycle, and 5 km run). Before and during the trials, participants were randomly provided with either placebo (PLA), low energy drink (Low ED), or high energy drink (High ED) supplement. Completion times in the High ED group increased significantly compared with the PLA and Low ED groups (p < 0.05). However, participants in the Low ED group also experienced an improved performance (p = 0.054). Analysis of variance revealed no differences between the three groups in cortisol and testosterone levels, or the Borg Rating of Perceived Exertion score (p > 0.5). Furthermore, significant differences in the levels of mononuclear cells, superoxide dismutase, and thiobarbituric acid reactive substances were observed between the PLA and High ED groups (p < 0.05). This indicates that energy drink consumption may improve performance and reduce oxidative stress in sprint triathlon athletes. However, individual differences should be considered when supplementing with energy drinks to decrease side effects.